Analytical cooperative entry guidance for Rendezvous and formation flight. (June 2020) - Yu, Wenbin; Yao, Yuzheng; Chen, Wanchun
Abstract: The cooperative entry guidance design is difficult for Hypersonic Glide Vehicles (HGVs), because the motions of hypersonic glider in longitudinal- and lateral-planes are seriously coupled as they lack adjustable thrust to offset the complex influence of lateral maneuvers on longitudinal motion, whereas formation flight requires that the two motions can be controlled independently. However, by exploring and exploiting the weak capability of HGVs in controlling the longitudinal and lateral motions independently, we propose a feasible flight mode named Rendezvous & Formation Flight (R&FF) mode, in which the vehicles are only required to fly in formation through a relatively short range. This flight mode is also of great value in fast cooperative detection of key area. The flight mode divides the entry flight into Rendezvous Phase (RP) and Formation Flight Phase (FFP), and the corresponding guidance scheme is designed to be of two layers: offline planning layer and online guidance layer. In the offline planning layer, the coordinated reference trajectories of all the vehicles for all the phases are fast planned beforehand by the mix use of the trajectory simulations and analytical solutions to 3-D hypersonic glide problem. In the online guidance layer, a weak-tracking guidance is posed for RP, which allows the HGVs to fly relatively freely for anti-interference, but should meet the rendezvous conditions strictly. By contrast, in FFP, a strong-tracking guidance is put forward to track the 3-D reference trajectories closely in order to maintain the formation configuration. Highlights: A Rendezvous & Formation Flight (R&FF) mode is proposed for Hypersonic Gliders. A two-layer cooperative entry guidance is designed for the R&FF mode. A hybrid planning scheme is designed to fast plan reference coordinated trajectories. A Bias Explicit Guidance (BEG) is developed to improve the rendezvous accuracy. An improved quasi-Newton method is proposed and proved theoretically.